Bonjour, butterfly - O'Connor, Jane; Preiss-Glasser, Robin (New York, NY : HarperCollins Childrens Books, 2008)
Nancy is furious when she cannot go to her friend Bree's butterfly-themed birthday party, but her family's outing might just be extraordinary enough to make her feel better. Includes facts about butterflies.
004-007.
Keywords: Butterflies -- Fiction; Parties -- Fiction; Birthdays -- Fiction